Far-Field, Radiation Resistance and temperature of Hertzian Dipole Antenna in Lossless Medium with Momentum and Energy Flow in the Far- Zone - Osama M. Abo-Seida; N.T.M.Eldabe; Ahmed Refaie Ali; Gamil.Ali Shalaby (JOURNAL OF ADVANCES IN PHYSICS, 2020)
A Far-field with calculation of intrinsic impedance, ohmic heating and antenna temperature of radiated ideal (Hertzian) dipole antenna have been discussed in free space and lossless background. Actually, there is great important to analysis the radiation resistance mechanism of a Hertzian dipole antenna in an infinite isotropic lossless medium. We also discussed the momentum and energy flow in electromagnetic fields with investigation that wavefront/phase velocity is equals to light speed in far zone. The temperature of lossless Hertzian antenna is equal to brightness temperature To.